2012
DOI: 10.1007/s00125-012-2716-9
|View full text |Cite
|
Sign up to set email alerts
|

A local glucagon-like peptide 1 (GLP-1) system in human pancreatic islets

Abstract: Aims/hypothesis Glucagon-like peptide 1 (GLP-1) is a major incretin, mainly produced by the intestinal L cells, with beneficial actions on pancreatic beta cells. However, while in vivo only very small amounts of GLP-1 reach the pancreas in bioactive form, some observations indicate that GLP-1 may also be produced in the islets. We performed comprehensive morphological, functional and molecular studies to evaluate the presence and various features of a local GLP-1 system in human pancreatic islet cells, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
194
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(215 citation statements)
references
References 50 publications
15
194
1
2
Order By: Relevance
“…It has, however, been thought that proglucagon is processed to glucagon in a-cells due to cell-specific expression of the processing enzymes prohormone convertase 2. However, as recently demonstrated by Marchetti et al in human islets, GLP-1 may also be expressed in a-cells (29). It has also been shown that under certain conditions, such as high glucose, GLP-1 production is increased in a-cells due to a specific overexpression of prohormone convertase 1/3 (30).…”
Section: Dpp-4 Inhibition In Pancreatic Isletsmentioning
confidence: 82%
“…It has, however, been thought that proglucagon is processed to glucagon in a-cells due to cell-specific expression of the processing enzymes prohormone convertase 2. However, as recently demonstrated by Marchetti et al in human islets, GLP-1 may also be expressed in a-cells (29). It has also been shown that under certain conditions, such as high glucose, GLP-1 production is increased in a-cells due to a specific overexpression of prohormone convertase 1/3 (30).…”
Section: Dpp-4 Inhibition In Pancreatic Isletsmentioning
confidence: 82%
“…Moreover, recent studies on glucose-dependent insulinotrophic polypeptide (GIP) and GLP1 have pointed out that both hormones are synthesized and secreted from islet α-cells under conditions of cellular stress imposed by β cytotoxic attack or increased insulin demand (Fujita et al 2010, Donath & Burcekin 2013, Moffett et al 2014. Increased expression of PC1/3 relative to PC2 in islet α-cells directs proglucagon processing away from glucagon towards GLP1 in these conditions (Wideman et al 2007, Marchetti et al 2012. As GLP1 and GLP2 are produced by the same convertase in equimolar amount (Janssen et al 2013), it is likely to hypothesize that GLP2 pancreatic expression also changes in stress conditions, such as derangements of islet cell function associated with prolonged consumption of HFD.…”
Section: Mechanistic Insightmentioning
confidence: 99%
“…In addition to influencing the pathophysiology on bone diseases caused by diabetes, bone density disorder in type 1 DM is also influenced by genetic factors (11). Also, increasing risk of fractures has been reported in diabetic patients treated with insulin drugs than non-insulin drugs (12). Considering importance of osteoporosis in the individual's activity and increased risk of pathological fractures in the future, determining prevalence and risk factors of the problem in children with type 1 DM and necessary treatments for its reduction is essential (13).…”
Section: Introductionmentioning
confidence: 99%